2021
DOI: 10.1177/21582440211023188
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors That Influence Consumer Intention to Use Mobile Money Services: An Application of UTAUT2 With Perceived Risk and Trust

Abstract: Mobile money is an attractive alternative that has boomed in recent times due to the advancement in mobile and telecommunication technology. Although there are copious benefits of such a great mobile technology, the adoption rate is far from expectations. This study examines the factors that predict users’ behavioral intention (BI) to adopt and use mobile money. The study adopts the unified theory of acceptance and usage of technology as a reference and builds an extended model by taking into account “perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 90 publications
(231 reference statements)
5
37
1
Order By: Relevance
“…Despite the tremendous recognition of UTAUT [ 25 ], Venkatesh et al [ 26 ] expanded the UTAUT model with the addition of three new factors, namely "price value", "hedonic motivation", and "habit", resulting in the establishment of the UTAUT2 theory. Previous studies revealed that compared to the original UTAUT, the extensions offered in the UTAUT2 resulted in a substantial increase in the explained variance (e.g., 56% to 74%) of the intention to adopt new technologies [ 27 ]. Taking all these facts into account, the UTAUT2 model was used in this study to examine the factors influencing the consumers’ intentions to embrace WPD in the context of China.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the tremendous recognition of UTAUT [ 25 ], Venkatesh et al [ 26 ] expanded the UTAUT model with the addition of three new factors, namely "price value", "hedonic motivation", and "habit", resulting in the establishment of the UTAUT2 theory. Previous studies revealed that compared to the original UTAUT, the extensions offered in the UTAUT2 resulted in a substantial increase in the explained variance (e.g., 56% to 74%) of the intention to adopt new technologies [ 27 ]. Taking all these facts into account, the UTAUT2 model was used in this study to examine the factors influencing the consumers’ intentions to embrace WPD in the context of China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…UTAUT and UTAUT2 were expanded by several studies [ 18 , 19 , 27 ] through the incorporation of perceived trust as an influencing factor of the intention to adopt contactless payments. According to other earlier studies, lifestyle compatibility was among the most important indicators of the intention to adopt contactless payment technologies [ 18 , 19 , 23 , 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations